3(1-2x)=.25(6x+9)

Simple and best practice solution for 3(1-2x)=.25(6x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-2x)=.25(6x+9) equation:


Simplifying
3(1 + -2x) = 0.25(6x + 9)
(1 * 3 + -2x * 3) = 0.25(6x + 9)
(3 + -6x) = 0.25(6x + 9)

Reorder the terms:
3 + -6x = 0.25(9 + 6x)
3 + -6x = (9 * 0.25 + 6x * 0.25)
3 + -6x = (2.25 + 1.5x)

Solving
3 + -6x = 2.25 + 1.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.5x' to each side of the equation.
3 + -6x + -1.5x = 2.25 + 1.5x + -1.5x

Combine like terms: -6x + -1.5x = -7.5x
3 + -7.5x = 2.25 + 1.5x + -1.5x

Combine like terms: 1.5x + -1.5x = 0.0
3 + -7.5x = 2.25 + 0.0
3 + -7.5x = 2.25

Add '-3' to each side of the equation.
3 + -3 + -7.5x = 2.25 + -3

Combine like terms: 3 + -3 = 0
0 + -7.5x = 2.25 + -3
-7.5x = 2.25 + -3

Combine like terms: 2.25 + -3 = -0.75
-7.5x = -0.75

Divide each side by '-7.5'.
x = 0.1

Simplifying
x = 0.1

See similar equations:

| 12x^3+28x^2+16= | | sinx=1/625pi^2 | | 15000+100n= | | 38-2[24/12*(4-1)^2] | | 4.8(-2)+43.1=22.7-5.4(-2) | | -4(n-6)=-5n | | 10x^6-26x^5-12x^4= | | 59/11 | | x-(17)=18 | | (-2.5x+1.14)-(.04x-.5)=a | | Y=ln(x-1)+ln(11-x) | | sinx=x^2/625pi^2 | | (6+z)(5z+1)=0 | | 21+3y-7=11y-10-2y | | A=b•h/2 | | 6(x-1/3)=2(x+23) | | 3=60-x | | -4(n+3)=-3n-2 | | 21-x=8 | | 3(4-8)=1/5(35x+30) | | -7(6+8r)-3r=17 | | 2y+x+-2x+3x=180 | | (1-x)+x=1.008 | | ln(7x-4)=lm(2x+11) | | 3x^3+7x^2+4x= | | 0.2(p+4)-0.7(p+2)=-3 | | 27x+21= | | (5x^2-30)/150x=1/6 | | a=22/7x45/2² | | 10-8(3-s)+5(s+3)=30 | | 30x^2-38x+12=0 | | 22/7(45/2)² |

Equations solver categories